Balancing Foreign Direct Investment and Minimum Wage Policy in Indonesia’s Batam Free Trade Zone: A SWOT Analysis - Sungkono Bayu Aji; Guntur Eko Saputro; Suwito Suwito (PPSDP International Journal of Education, 2026)
This study examines the complex relationship between foreign direct investment (FDI) and minimum wage policy as strategic factors in Batam, Indonesia’s largest Free Trade Zone (FTZ). Using a qualitative approach, we conducted a SWOT (Strengths, Weaknesses, Opportunities, Threats) analysis based on government regulations, secondary economic data (2015–2025), and industry reports. The findings reveal that while Batam’s strategic location, fiscal incentives, and labor abundance attract FDI, rising minimum wage demands driven by high living costs threaten its cost competitiveness relative to Vietnam and Thailand. Institutional dualism (local government vs. Batam Investment Agency) further complicates policy coordination. We conclude that Batam is shifting from a low-wage to a productivity-driven competitiveness model. Policy implications include the need for integrated governance, skill upgrading, and infrastructure investment to sustain FDI without suppressing workers’ welfare.